(untitled) (Світ фінансів, 2017)
Сіташ Т. Д. Удосконалення фінансового планування в закладах охорони здоров’я. Обґрунтовано альтернативи фінансового планування охорони здоров’я в Україні. Охарактеризовано три види фінансового планування галузі: стратегічне, поточне та оперативне. Виявлено проблеми охорони здоров’я та запропоновано альтернативні напрями їх вирішення. Sitash T. Perfection of financial planning of health protection. The alternatives of the financial planning of health protection in Ukraine are reasonable. Three types of the financial planning of industry are described: strategic, current and operative. The problems of health protection are educed and alternative directions of their decision are offered.